2017
DOI: 10.18203/2394-6040.ijcmph20175333
|View full text |Cite
|
Sign up to set email alerts
|

Community medicine: perceptions among medical students and career preference: a cross sectional study

Abstract: Background: Learning community medicine helps the student not only to become a good clinician but also a good manager, educator and a researcher. Community medicine exposes medical students to primary and secondary healthcare settings and to promotive, preventive, curative and rehabilitative health services. This helps them to serve the needy people with a holistic approach. The objective is to find the perceptions of medical students regarding Community Medicine as a Medical Subject and as a career preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…14,15 In our study, 93.9% showed a positive attitude in gaining skills to understand the research in their period of CM postings same results were obtained in Sadawarte et al and they stated that this is crucial because the more innovation and enhance have conducting medical research, to better their knowledge of literature reviews, critical evaluation of research papers, and report writing. 16 Our study shows that 89.7% suggested having an understanding of concepts in CM followed by preventive measures against diseases (86.6%), the reallife health issues of the community (85%), whereas Murugavel et al reported that 83% for understanding the concepts of CM, 80.7% preventive measures against disease and 79.8% real-life health issues. 14 Communitybased learning programs that use various approaches to expose students to the structure, functioning, and perceived needs of the community may play a major impact in increasing students' enthusiasm for learning and choosing a career option.…”
Section: Discussionmentioning
confidence: 61%
“…14,15 In our study, 93.9% showed a positive attitude in gaining skills to understand the research in their period of CM postings same results were obtained in Sadawarte et al and they stated that this is crucial because the more innovation and enhance have conducting medical research, to better their knowledge of literature reviews, critical evaluation of research papers, and report writing. 16 Our study shows that 89.7% suggested having an understanding of concepts in CM followed by preventive measures against diseases (86.6%), the reallife health issues of the community (85%), whereas Murugavel et al reported that 83% for understanding the concepts of CM, 80.7% preventive measures against disease and 79.8% real-life health issues. 14 Communitybased learning programs that use various approaches to expose students to the structure, functioning, and perceived needs of the community may play a major impact in increasing students' enthusiasm for learning and choosing a career option.…”
Section: Discussionmentioning
confidence: 61%
“…Almost all the students stressed that more practical topics should be covered and teaching methodology needs to be modified to make the topic more interesting. [ 4 ] In this study, we found a significant increase in the understanding and interest toward the subject after giving a community exposure to the students. A significant increase in the scoring of the students with every field visit was also observed, which highlights that the community visits also help enhance the soft skills of the students like communication skills, how to elicit history, team spirit, and attitude toward the community.…”
Section: Discussionmentioning
confidence: 63%
“…In the study by Sadawarte, majority of students (96.8%) agreed that more practical training need to be added to the curriculum. 12 This was also noted in the study on teaching methods in Community Medicine by Sharma et al where 76% of students opined that field visits are major contributing factors to enhance their practical skills. 13 This is also discussed in already published literature which stresses shifting the emphasis towards family visits, demographic and morbidity surveys, community diagnosis and research projects.…”
Section: Discussionmentioning
confidence: 64%
“…14 In the study done among medical students in Mumbai, 40% opted Community Medicine for their career, which is in contrast to the 12% in this study. 12 Murugavel et al in their study done in a Private Medical College in Chennai reported that 21.8% expressed interest in specializing in Community Medicine. 10 In a study by Kar et al, the authors reported that Community Medicine and Psychiatry were not preferred by students as their career choice and stressed upon the need to enhance the students" interest in these subjects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation